Retinal Microvascular Calibers Are Associated With Enlarged Perivascular Spaces in the Brain. Issue 5 (May 2016) - Mutlu, Unal; Adams, Hieab H.H.; Hofman, Albert; Lugt, Aad van der; Klaver, Caroline C.W.; Vernooij, Meike W.; Ikram, M. Kamran; Ikram, M. Arfan
Abstract : Background and Purpose—: Perivascular enlargement in the brain is a putative imaging marker for microvascular brain damage, but this link has not yet been confirmed using direct in vivo visualization of small vessels. We investigated the relation between microvascular calibers on retinal imaging and enlarged perivascular spaces (ePVSs) on brain magnetic resonance imaging. Methods—: We included 704 participants from the Rotterdam study. Retinal arteriolar and venular calibers were measured semiautomatically on fundus photographs. ePVSs were counted in the centrum semiovale, basal ganglia, hippocampus, and mesencephalon, using a standardized rating method. We determined the association between retinal microvascular calibers and ePVSs with negative binomial regression models, adjusting for age, sex, the other vascular caliber, structural brain magnetic resonance imaging markers, and cardiovascular risk factors. Results—: Both narrower arteriolar and wider venular calibers were associated with more ePVSs in the centrum semiovale and hippocampal region. Rate ratios (95% confidence interval) for arterioles in the centrum semiovale and hippocampus were 1.07 (1.01–1.14) and 1.13 (1.04–1.22), respectively, and for venules 1.08 (1.01–1.16) and 1.09 (1.00–1.18), respectively. These associations were independent from other brain magnetic resonance imaging markers and cardiovascular risk factors. Conclusions—: Retinal microvascular calibers are related to ePVSs, confirming the putative link between microvascular damage and ePVSs. Abstract : Supplemental Digital Content is available in the text.